1983
DOI: 10.1111/j.2044-8279.1983.tb02552.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Locus of Control to Self‐esteem, Academic Achievement, and Prediction of Performance Among Nigerian Secondary School Pupils

Abstract: The purpose of this study was: (a) to investigate the effects of socioeconomic background, locus of control, intelligence, and self-esteem on academic achievement of Nigerian secondary school pupils; (6) and to examine the relationships of locus of control to socioeconomic background, intelligence, self-esteem, academic achievement and prediction of academic performance. Eighty secondary school boys completed the Socio-economic Background Questionnaire, the Raven's Standard Progressive Matrices, the Brookover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2
9

Year Published

1984
1984
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
3
15
2
9
Order By: Relevance
“…This finding contradicts the notion that high internal locus of control is associated with high ability (e.g. Willey, 1978;Brown, 1980;Maqsud, 1983;McLaughlin & Saccuzzo, 1997). The finding is, however, in line with the findings of Nowicki and Duke (1983).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This finding contradicts the notion that high internal locus of control is associated with high ability (e.g. Willey, 1978;Brown, 1980;Maqsud, 1983;McLaughlin & Saccuzzo, 1997). The finding is, however, in line with the findings of Nowicki and Duke (1983).…”
Section: Discussioncontrasting
confidence: 80%
“…High internal locus of control is associated with high intelligence (e.g. Brown, 1980;Maqsud, 1983;Willey, 1978). In their study of fifth to seventh graders, McLaughlin and Saccuzzo (1997) found a more internal locus of control in gifted children.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with Internal Locus of Control attribute the cause of events in their lives to their own actions whereas individuals with External Locus of Control assume these events to be determined by external forces. Various researchers have shown a significant relation between Locus of Control and academic achievement: students with Internal Locus of Control tend to have better grades and receive higher achievement-test scores than External Locus of Control students (Johnson & Kanoy, 1980;Kennelly & Mount, 1985;Maqsud, 1983;Stipek & Weisz, 1981). Skinner and colleagues (Chapman, Skinner, & Baltes, 1990;Skinner, Chapman, & Baltes, 1988a, 1988bSkinner, Wellborn, & Connell, 1990) have proposed that a key component in students' beliefs about Locus of Control is their level of motivation in academic tasks.…”
Section: Who Is Vulnerable To Stereotype Threat?mentioning
confidence: 96%
“…to enable the pupil to take responsibility for his/her own learning. Maqsud (1983) demonstrates that this is a significant factor in academic achievement. It should enable pupils to experience autonomy in the way they lived their lives and in the way they learned.…”
Section: It's Who You Are Not What You Do That Makes a Differencementioning
confidence: 95%